ENHANCING PATIENT SATISFACTION: A COMPREHENSIVE REVIEW OF MEDICAL STAFF’S INTEGRATIVE ROLES AND PRACTICES - Mohammed Hussain Mohammed Alofayr, Jaber Ali Bani Humayyim , Hussein rakan al sherif, Mohammed abdullah ali al Sulayyim , Mohammed Ali Bani Hamaim, Saeed Awadh Ali Bani Humayyim , Fahad Zamil Ali Alyami, Turky Ali H Bnihamim (Chelonian Research Foundation, 2022)
In the contemporary healthcare landscape, achieving high levels of patient satisfaction is imperative for the success and reputation of medical institutions. This critical review explores the integrative roles of medical staff, including physicians, nurses, allied health professionals, and support staff, in enhancing patient satisfaction. The paper highlights the significance of a patient-centered care approach, emphasizing effective communication, empathy, and interdisciplinary collaboration as key factors in improving patient experiences. Through a synthesis of current literature, this review identifies best practices and innovative strategies that medical professionals can employ to address the complex needs and expectations of patients. The importance of environmental factors, administrative efficiency, and the use of feedback mechanisms for continuous improvement are also examined. This article aims to provide healthcare professionals and administrators with insightful recommendations on fostering a healthcare environment that prioritizes patient satisfaction, ultimately leading to better patient outcomes and increased healthcare quality. Keywords: Patient Satisfaction, Patient-Centered Care, Interdisciplinary Collaboration, Medical Staff Roles, Communication in Healthcare, Healthcare Quality, Empathy, Patient Engagement, Continuous Improvement, Healthcare Environment.